Low-Dose Aspirin-Associated Upper and Mid Gastrointestinal Tract Damage and Gene Polymorphism - Shiotani, Akiko; Fujita, Yoshihiko; Nishio, Kazuto (Current Pharmaceutical Design, 2015)
The risk of gastrointestinal (GI) bleeding is increased in association with the use of low-dose aspirin (LDA). There are few studies of the association between genetic polymorphisms and the risks of aspirin-induced ulcer or its complications. Individuals with two single nucleotide polymorphisms (SNPs) of cyclooxygenase-1 (COX-1), A-842G and C50T, exhibit increased sensitivity to aspirin and lower prostaglandin synthesis capacity but the polymorphism lacked statistical significance in relation to an association with bleeding peptic ulcer. In our previous Japanese study, SLCO1B1 521TT genotype and the SLCO1B1 *1b haplotype were significantly associated with the risk of peptic ulcer and ulcer bleeding in patients taking LDA, especially in the patients with angiotensin converting enzyme inhibitor (ACEI), angiotensin type 1 receptor blocker (ARB), or statin co-treatment. Protonpump inhibitors (PPIs) are recommended for patients who require antiplatelet therapy and have a history of upper GI bleeding. The interaction between PPIs and consequent impaired effectiveness of clopidogrel has caused concern regarding the effect of genetic polymorphisms of the CYP2C19 which mediates conversion of clopidogrel to its active metabolite. The later recent genome-wide analysis of SNPs indicated the association of several SNPs with small bowel bleeding in Japanese patients taking LDA. The data are still lacking and further prospective studies are needed to identify the specific gene polymorphisms as risk or protective factors for GI bleeding associated with LDA.
Keywords: and CHST2